2003
DOI: 10.1099/mic.0.26307-0
|View full text |Cite
|
Sign up to set email alerts
|

pGIL01, a linear tectiviral plasmid prophage originating from Bacillus thuringiensis serovar israelensis

Abstract: Bacillus thuringiensis serovar israelensis harbours, in addition to several circular plasmids, a small linear molecule of about 15 kb. Sequence analysis of this molecule, named pGIL01, showed the presence of at least 30 ORFs, five of which displayed similarity with proteins involved in phage systems: a B-type family DNA polymerase, a LexA-like repressor, two potential muramidases and a DNA-packaging protein (distantly related to the P9 protein of the tectiviral phage PRD1). Experimental evidence confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 47 publications
(36 reference statements)
4
91
0
Order By: Relevance
“…A dot blot analysis revealed the presence of molecules related to GIL01 in five strains of the B. cereus group (B16, B23, DBT012, BGSC4D14, and Bt5), and a subsequent PCR analysis using GIL01-specific primers showed that these elements possess different PCR patterns (28). Further experiments performed with the linear molecule harbored by strain B16 showed that it actually corresponds to the prophage form of a temperate phage named GIL16.…”
Section: Gil16 Is Morphologically Similar To Other Tectiviral Phagesmentioning
confidence: 99%
See 3 more Smart Citations
“…A dot blot analysis revealed the presence of molecules related to GIL01 in five strains of the B. cereus group (B16, B23, DBT012, BGSC4D14, and Bt5), and a subsequent PCR analysis using GIL01-specific primers showed that these elements possess different PCR patterns (28). Further experiments performed with the linear molecule harbored by strain B16 showed that it actually corresponds to the prophage form of a temperate phage named GIL16.…”
Section: Gil16 Is Morphologically Similar To Other Tectiviral Phagesmentioning
confidence: 99%
“…GIL16 is able to produce small turbid plaques on B. thuringiensis GBJ002, which is also the native host for GIL01 (28). In order to avoid any contamination by other bacteriophages potentially present in strain B16, we isolated B. thuringiensis GBJ002 lysogens for GIL16 and confirmed the presence of the pGIL16 prophage by PCR.…”
Section: Gil16 Is Morphologically Similar To Other Tectiviral Phagesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Middle East, the natural occurrence of B. thuringiensis in soil environments was reported from Egypt [31] and Jordan [39]. One of the efficient producers of biological insecticides is Bt which is used in industrial application by many Government and Companies [46]. However, sensitivity of Bt to lysis by bacteriophages is the most one of complicated to such industry.…”
Section: Introductionmentioning
confidence: 99%